Correlation of Hemoglobin Levels with VO₂ Max in Adolescent Basketball Athletes - Febi Irawati, Andi; Hammado, Nurul Ichsania (Universitas Negeri Jakarta, 2025)
Hemoglobin serves as a key determinant in oxygen transport to peripheral tissues, thereby directly influencing aerobic capacity, typically assessed via maximal oxygen uptake (VO₂ Max). In basketball, a sport characterized by a unique integration of aerobic and anaerobic demands, maintaining optimal hemoglobin concentration is critical for sustaining high-level performance. This study aimed to examine the association between hemoglobin concentration and VO₂ Max in competitive basketball athletes. A quantitative correlational design with a cross-sectional approach was employed. Twenty basketball athletes (12 male, 8 female), aged 19–23 years, were recruited through purposive sampling. Hemoglobin concentration was assessed using digital hematology analysis, while VO₂ Max was estimated through the Multistage Fitness Test. Data were analyzed using Pearson’s product–moment correlation with a significance threshold of p < 0.05. The mean hemoglobin concentration was 14.73 ± 1.27 g/dL, and the mean VO₂ Max was 51.89 ± 5.32 mL·kg⁻¹·min⁻¹. Statistical analysis demonstrated an exceptionally strong positive correlation between hemoglobin concentration and VO₂ Max (r = 0.993, p < 0.001), indicating that higher hemoglobin levels are closely linked to enhanced aerobic capacity. These findings underscore the pivotal role of hemoglobin monitoring in athlete fitness evaluation and suggest its potential utility as a biomarker for targeted performance optimization strategies in basketball.